Case Report: Neuroretinitis following combination checkpoint inhibition therapy with nivolumab and ipilimumab for stage IIIC melanoma - Nuha S. Arefin; Jared Moon; Aaron B. Roller; Moe H. Aung (Frontiers in Oncology, 2026)
Purpose Neuroretinitis is a very rare but recognized immune-related adverse event (irAE) of immune checkpoint inhibitor (ICI) therapy. We present a case of likely ICI-associated neuroretinitis following combination nivolumab and ipilimumab treatment for stage IIIC cutaneous melanoma. Observations Our patient is a 48-year-old woman with stage IIIC melanoma who developed acute left eye vision loss approximately three months after initiating nivolumab and ipilimumab, near the end of a corticosteroid taper for a concurrent systemic irAE. Examination showed best-corrected visual acuity of 20/400, severely reduced color vision (2/14 Ishihara plates), and a relative afferent pupillary defect in the left eye. Initial fundus exam of that eye revealed optic disc edema with nasal hemorrhages as well as peripapillary macular edema. There was a central scotoma with nasal steps on the Humphrey visual field (mean deviation -13.24 dB). Fluorescein angiography demonstrated disc leakage with inferior arcuate hypoperfusion. Optical coherence tomography (OCT) showed subsequent intraretinal exudates in the nasal macula bilaterally, worse in the left eye. Infectious workup and neuro-imaging were unremarkable. The patient was treated with intravenous methylprednisolone (IVMP) pulse and intravenous immunoglobulin (IVIG) at initial hospitalization, followed by a slow oral prednisone taper along with monthly IVIG outpatient. Her visual acuity in the left eye improved to 20/20 at 6-month follow-up visit. Conclusions and importance ICI-associated neuroretinitis is rare but vision-threatening and may emerge or worsen during systemic corticosteroid tapering for concurrent irAEs. Prompt recognition, exclusion of infectious mimics, and multidisciplinary management can yield meaningful visual recovery. Comprehensive neuro-ophthalmic assessment for ICI-associated neuro-ophthalmic complications including evaluation of color vision and pupillary function, documentation of fundus appearance, and additional ancillary testing with visual field and OCT analysis is essential.